Metaphysics and Religious Education in Primary School – Readiness for the concept of “diakoultouralismos” - Portelanos, Stamatis; Polyzou, Marianthi (Advances in Social Sciences Research Journal, 2016)
The existence of “Collective Unconscious” that contains the inherent human tendency to seek truth and the will for good, composes the “intercultural metaphysics”. The universality of metaphysics appears in every culture, in every person and age. Metaphysics and religiousness are connected with pedagogy, as well with psychology which is referred to the human unconscious “archetypes”. The existential questions appear from childhood and find answers in the history of religious and cultural expression of all the people worldwide. Therefore, the access to the culture’s ontology is elliptical, and also every educational plan for education without the metaphysical knowledge of human nature is deficient and imperfect. Pedagogy draws intercultural and “diakoultouralistic” content from any civilization and culture, in cases interested to integrate to the Curriculum topics that include experiences of mental and moral ethics. Recalling the existential and social reflection of Metaphysics and religion’s history provide an opportunity for the discovery of both the substance of life and the meaning of human existence and human relations. The appropriate use of a religion’s universal values eliminates the religious competition or cultural conflict and promotes the concept of “diakoultouralismos”. An essential chapter of any national education is the distinction awareness of the distinction between what “seems to be” and what it finally “is”, giving examples and authentic narratives of the familiar and world culture. Moreover, the memory of faiths’ and beliefs’ standards, which hypostatize universal virtues and values of life in connection with historical facts, are timeless hopes and inherent clues of education.